Portable Electronic Warp Load Meter - Sivadas, T. K. (Fishery Technology, 1978)
A portable type warp load meter has been developed for the use in fishing trawlers. The instrument enables to monitor the warp load in fishing trawlers accurately and easily without disturbing the routine fishing operations. The instrument can be used in several other places like cranes, bollard tests for marine engines. dry docks etc. especially when the operation has to be conducted easily without disturbing the load system. The information displayed in microammeter in the range 0 to 1000 kg can be fed to continuous recorders for detailed analysis and permanent records.